Analisis Pengaruh Umur, Paritas, dan Motivasi Suami terhadap Nyeri Persalinan di Cirebon Tahun 2019 - Liliek Pratiwi; Tita Hustinawati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2020)
Background : Mothers who experience childbirth will feel pain. Labor pain is an unpleasant sensory and emotional experience due to tissue damage. In Indonesia Health Profile Data in 2018, there are 4643 Health Centers that work together through the health departement with blood transfusion units and hospitals in blood services to reduce maternal mortality. It is an effort of the health service the it is also necessary en effort from the family, especially the husband. Other factors need to be assessed for what affects labor pain. In 2015, maternal mortality rate especially in Cirebon, is 4 people on 5409 live birth. So, in this study will be seen again which factors that influence labor pain. Objective : Literature studies and preliminary studies were conducted to further examine and describe the experience of mothers through childbirth in Cirebon. Method : The design of this research is descriptive research. In this study, an analysis will be conducted, namely analysis of the influence, age, parity and motivation of husbands on the healing of special births in Cirebon District, which will be carried out using descriptive methods in which the data collection process allows the research to produce a description related to this study. The sampling technique in this research is criterion-based selection sampling, because the sample selection is based on certain unique criteria.Result and Discussion : The results of the study are there are 5 categories such as husband character husband’s treatment when the mother is giving birth, number of children, husband’s motivation and back massage from husband. From 10 informans, 7 primigravida with an average age of 28 years, in her experience felt very experiencing labor pain even though her husband provided motivation without treatment during the process of giving birth. The character of multigravida mothers as informan 3,4,and 5. They are on average 36 years old., 2 informans stated, they didn’t not feel pain because their husbands motivated and facilitated pain managements like back massage. Conclusion : The conclusion of this research is that all health workers who focus on reproductive health, to be more pro active in facilitating mothers who will give birth. Then matenity women, especially in Cirebon better get the assistance of their husband and family as applying the theory of family center maternity care. The outcome of this study is related to the Cirebon District Health Office's mission, which is to improve the ability, quality and professionalism of the health provider, optimize health services to the community, and create a healthy community.